Global Warming, Climate Variability Influences, and Destitution in Emerging Nations - B Satheesh (Global Journal of Plant and Soil Sciences, 2024)
This essay started with discussing the similarity and difference of climate variability and climate change and it was noted that these are inseparable. Discussions and debates along with pledges to help emerging nations to curtail GHGs were also tackled. Re- nown people have talked and reminded the UN Conference that the longer no action is taken to solve this, self-extermination may result (Araujo, 2000; Dankelman and Davidson, 2013). Just this week a young lady forcefully talked to the world leaders to change their course of steering the world boat which if the thinking is to gain riches then we all are to perish. For poor countries vis-à-vis guinea pigs where some new and vital innovations are brought in for trials, demonstrations and experiments, time and opportunities avail to us to take advantage of (Gueron, 2017). Destitution cannot be overemphasised as on daily basis many Africans are leaving their own countries for Europe perhaps to get a better life Social learning is one approach that can solve the challenges faced by both illiterate and educated farmers.